A participação de professores de matemática e análise de materiais curriculares elaborados em um trabalho colaborativo - Costa, Wedeson Oliveira (2015)
The aim of this work is to analyze how math teachers participate in the development of mathematical tasks that constitute an educational curriculum material in a collaborative work and to analyze mathematical tasks produced by these teachers in this context. Thus, the focus of this research is the participation of teachers and the production of mathematical tasks. Thereby, theoretical constructs presented by Jean Lave and Etienne Wenger were used to understand the participation of teachers and tasks markers presented by Jonei Barbosa used as reference for the analysis of mathematical tasks. The context of this research were the meetings of the Mathematics Educational Watch (OEM-Bahia) based at the Federal University of Bahia (UFBA) and formed by teachers (basic and college education) and students with Degree in Mathematics and Post-Graduate at the State University of Feira Santana and Federal University of Bahia. The methodological approach was qualitative, in which we used as procedures of data collection observation and interviews stimulated for analyzes relating to the participation of teachers, and document analysis of mathematical tasks that constitute an educational curriculum materials developed by teachers during the collaborative work. The results showed that the participation of teachers in the development of mathematical tasks occurs in three distinct ways: contemplating common goals of the group, sharing ways to develop investigative or exploratory mathematical questions and producing tasks in view of the practices involving other math teachers. Ways to participate relate to the joint undertaking established by the group for the preparation of tasks, with the list shared repertoire group members, which allowed evidence of changes in practices in which teachers participate and with what the group reifies from participation in social practice. In terms of the tasks that were developed through the participation of teachers in the OEM-Bahia we can see that the mathematical tasks performed in convergent, divergent and alternate forms, depending on the task markers, allowing an analysis of the freedom of choice of group during the design of tasks, depending on the practice that teachers involved and the context of the classroom. In terms of mathematical tasks markers, the analysis allowed us to expand the theoretical construct, indicating the possibility of tasks with alternative insulation because the relationships established during the implementation of tasks can be in charge of teachers and negotiations with the students. In addition, we propose the marker in relation to the procedures that are required from students during the implementation of mathematical tasks, called teaching focus. This analysis allowed us to realize that both tasks markers as the framework for analyzing mathematical tasks theoretically allow further analysis of mathematical tasks designed in different contexts and social practices.